Radial profile and precipitation uniformity of sprinkler NaanDanJain 427, depending on the setting of the deflector - Martins, Paulo E.S. [UNESP]; Zanini, José R. [UNESP]; da Silva, Elcides R. [UNESP]; Lemos Filho, Marco A.F. [UNESP] (FapUNIFESP (SciELO), 2012)
The study aimed to evaluate the radial profile and the uniformity of water distribution of sprinkler manufactured by the company NaanDanJain, model 427 1/2M and nozzle with 2.8 mm of internal diameter, operating at pressures of 150, 200, 300 and 400 kPa and five positions of the deflector (0, 20, 50, 80 and 100%). For the determination of the parameters evaluated, the grid method was used and with the help of computer application CATCH 3D, overlapping layers of water depths was calculated with ten spacing. The results show that the deflector adjustment influences the radius of wetness and the distribution profile while the uniformity of water application showed as an important mechanism, since it permits different behavior for the sprinkler, ensuring wide track of utilization of the equipment.
Perfil radial e uniformidade de precipitação do aspersor NaanDanJain 427, em função da regulagem do defletor
Keywords: Hydraulic performance; Irrigation uniformity; Water distribution profile